1978
DOI: 10.1073/pnas.75.4.1877
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of cholesteryl ester formation in human fibroblasts by an analogue of 7-ketocholesterol and by progesterone

Abstract: The synthesis of cholesteryl esters in cultured human fibroblasts is catalyzed by a microsomal acyl-coenzyme A:cholesterol acyltransferase (EC 2.3.1.26

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

1980
1980
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Additionally, preputial gland size in both male and female rats is increased by progesterone, while estrogen stimulates lipid synthesis, including that of sterol esters, in female rat preputial gland cells (42). At this point we do not know how steroid hormone administration affects mouse ACAT mRNA levels in vivo, but progesterone has been shown to inhibit ACAT activity in cultured fibroblasts (43), rabbit ovary (44), and rat liver microsomes (14,45). Thus it is possible that ACAT expression is steroid hormone-responsive in vivo and that hormonal regulation of ACAT is involved in the development of certain specialized cells such as the sebocyte.…”
Section: Figmentioning
confidence: 94%
“…Additionally, preputial gland size in both male and female rats is increased by progesterone, while estrogen stimulates lipid synthesis, including that of sterol esters, in female rat preputial gland cells (42). At this point we do not know how steroid hormone administration affects mouse ACAT mRNA levels in vivo, but progesterone has been shown to inhibit ACAT activity in cultured fibroblasts (43), rabbit ovary (44), and rat liver microsomes (14,45). Thus it is possible that ACAT expression is steroid hormone-responsive in vivo and that hormonal regulation of ACAT is involved in the development of certain specialized cells such as the sebocyte.…”
Section: Figmentioning
confidence: 94%
“…In addition, cholesterol esterification in vitro varies with the availability of cholesterol to the undersaturated enzyme (3,25,26). Furthermore, a parallel has been demonstrated between the rate of cholesterol esterification in vivo and that in the corresponding unfractionated membranes from cells treated with LDL (6), acetylated LDL (27), progesterone (28), or oxysterols such as 25-HC (6,29). While these results are consistent with the premise that in vitro esterification manifests the pool of cholesterol in the ER, other mechanisms could obscure this relationship.…”
mentioning
confidence: 99%
“…Chloroquine also prevented the activation of ACAT by VLDL (Table 1). These findings indicate that VLDL are degraded in the lysosomes similar to LDL degradation in human skin fibroblasts (Goldstein et al, 1978). The experiments with preadipocytes from human fat tissue showed that these cells bind and metabolize LDL more efficiently than VLDL.…”
Section: Resultsmentioning
confidence: 55%
“…The results shown in Table 2 indicate that the rat preadipocytes bind, internalize, and degrade human VLDL nearly three times more than human LDL. To investigate the involvement oflysosomal degradation in the metabolism of lipoproteins in these cells, the effect of chloroquine, which is known to inhibit the lysosomal enzymes by increasing the intralysosomal pH, was studied (Goldstein et al, 1978). When After the preadipocytes were incubated with medium containing LPDS for 48 h, the medium was removed and replaced with fresh medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation